Britain's political economies : Parliament and economic life, 1660-1800 - Hoppit, Julian (Cambridge : Cambridge University Press, 2017)
The Glorious Revolution of 1688-9 transformed the role of parliament in Britain and its empire. Large numbers of statutes resulted, with most concerning economic activity. Julian Hoppit here provides the first comprehensive account of these acts, revealing how government affected economic life in this critical period prior to the Industrial Revolution, and how economic interests across Britain used legislative authority for their own benefit. Through a series of case studies, he shows how ideas, interests, and information influenced statutory action in practice. Existing frameworks such as'mercantilism' and the'fiscal-military state' fail to capture the full richness and structural limitations of how political power influenced Britain's precocious economic development in the period. Instead, finely grained statutory action was the norm, guided more by present needs than any grand plan, with regulatory ambitions constrained by administrative limitations, and some parts of Britain benefiting much more than others.
Title from publisher's bibliographic system (viewed on 25 May 2017).
Keywords: Great Britain -- Economic policy; Great Britain -- Economic conditions; Great Britain -- Politics and government -- 1660-1714.; Great Britain -- Politics and government -- 18th century